2000
DOI: 10.1017/s0021859699008151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannic acid on rumen degradation and intestinal digestion of treated soya bean meals in sheep

Abstract: SUMMARYThe current experiment was conducted to study the effect of different doses of tannic acid, a hydrolysable tannin, on ruminal degradation and post-ruminal digestion of treated soya bean meals (SBM) in sheep. Samples of SBM were prepared by spraying 100 g SBM with 100 ml distilled water containing 0, 1, 5, 10, 15 or 25 g of commercial tannic acid (S ! , S TA" , S TA# , S TA$ , S TA% and S TA& , respectively). Three ruminally cannulated ewes, that had never consumed tannic acid previously, were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
4
25
0
3
Order By: Relevance
“…Spraying TA on alfalfa before ensiling affected neither N concentration nor effective degradability of crude protein (CP) but reduced the percentage of CP solubilised at initiation of incubation (Santos et al, 2000). However, soya bean treatment with TA reduced ruminal degradation and intestinal digestibility of proteins (Hervas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spraying TA on alfalfa before ensiling affected neither N concentration nor effective degradability of crude protein (CP) but reduced the percentage of CP solubilised at initiation of incubation (Santos et al, 2000). However, soya bean treatment with TA reduced ruminal degradation and intestinal digestibility of proteins (Hervas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its availability, cost and relative purity, tannic acid has been used widely to study the effect of tannins on rumen fermentation (Driedger et al, 1969;Nishimuta et al, 1974;Murdiati et al, 1992;Zhu and Filippich, 1992;Plumlee et al, 1998;Hervas et al, 2000;Santos et al, 2000;Frutos et al, 2004;Martinez et al, 2005 and. The objective of this study was to assess the influence of spraying tannic acid (TA) on chopped alfalfa hay on in vitro rumen fermentation of dry matter (DM) and N retention by sheep fed alfalfa hay.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of tannins on protein degradation is basically a reduction in the immediately degradable fraction, and a reduction of the fractional rate of degradation (Aharoni et al, 1998;Frutos et al, 2000;Hervás et al, 2000).…”
Section: Ruminal Fermentationmentioning
confidence: 99%
“…Pace et al (1993) observed that the CT of quebracho provoked a greater reduction in the degradability of soya bean meal than commercial tannic acid, but in general the results obtained were very variable and depended on many factors. Hervás et al (2000) and Frutos et al (2000) treated soya bean meal with different doses (0, 1, 4.7, 9, 13 and 20%) of tannic acid or commercial quebracho CT extract, and significantly reduced the extent of crude protein degradation in the rumen. The effect was significant even at the lowest dose.…”
Section: Practical Use Of Tannins Treatments To Protect Dietary Protementioning
confidence: 99%
“…Ante el deseo de mejorar el contenido de proteína láctea, y por lo tanto aumentar la calidad de la leche, es importante explorar nuevas estrategias en los sistemas de alimentación; que contribuyan a incrementar la eficiencia en la fermentación y de esta manera asegurar niveles adecuados de amonio ruminal, ayudando a mejorar la actividad para la síntesis de proteína bacteriana y sobrepasante (Hervás, et al, 2000). Ambos aspectos impactan de manera positiva la disponibilidad de aminoácidos para el rumiante lo que puede generar un mejor nivel proteico en la leche (Hervás et al, 2001).…”
Section: Uso Potencial De La T Diversifolia En Sistemas Lecheros De unclassified